Penerapan Terapi Genggam Jari untuk Menurunkan Tingkat Nyeri pada Pasien Selulitis Pedis dengan Komplikasi Diabetes Mellitus: Laporan Kasus - Mulyana, Egi Andrian; Haryeti, Popon (Wiraraja Medika : Jurnal Kesehatan, 2025)
Diabetes mellitus increases patients’ vulnerability to cellulitis due to impaired circulation, neuropathy, and reduced immunity, which lead to symptoms such as redness, pain, and swelling in the affected area. To help relieve this discomfort, the finger-hold relaxation technique has begun to be used as a simple non-pharmacological method because it provides a calming effect and helps reduce pain intensity. This study aimed to determine the effectiveness of the finger-hold relaxation technique in reducing pain levels in patients with pedal cellulitis and diabetes mellitus complications. The study combined an evidence-based nursing practice approach with a case study design. The subject was a female patient who received four days of treatment at Umar Wirahadikusumah Regional General Hospital in Sumedang for pedal cellulitis and diabetes-related complications. The findings showed a gradual decrease in pain intensity from 6 to 1 over four days. The patient also reported increased comfort and improved sleep quality. Conclusion: The finger-hold relaxation technique is effective in reducing pain in patients with cellulitis and diabetes complications.